Anti-CD40 Antibodies do not Cause Thromboembolism as Demonstrated by in Vitro and in Vivo Studies. (July 2018) - Rubic-Schneider, Tina; Christen, Brigitte; Garcia, Deborah; Loll, Nathalie Runser; Erard, Esther; Flandre, Thierry; de Billy, Benjamin Cochin; Nock, Sebastien; Côté, Serge; Rush, James S; Ulrich, Peter
Abstract : Clinical trials with non-silenced anti-CD40L (anti-CD154) monoclonal antibodies (mAb) in patients with systemic lupus erythematosus (SLE) and idiopathic thrombocytopenic purpura (ITP) were halted after unexpected fatal thromboembolic events (TE). Previous results have shown that soluble CD40L/anti-CD40L mAb immune complexes (IC) can activate and induce pro-aggregatory effects on platelets in vitro via FcgRIIa. Pulmonary thrombi consisting of platelet aggregates and fibrin, and thrombocytopenia were found in humanized FcgRIIa transgenic mice after injection of pre-formed IC consisting of mouse soluble CD40L and anti-mouse CD40L mAb. To date, no such studies have been performed with IC of mouse sCD40 and anti-mouse CD40 mAbs. We therefore injected either single mouse proteins (soluble CD40L, soluble CD40) or antibodies (isotype controls, anti-mouse CD40L mAb, anti-mouse CD40 mAb), IC of soluble protein with the respective antibody into humanized FcgR transgenic mice. In addition, in vitro platelet aggregation was performed using blood from FcgR transgenic mice and human healthy donors. Whole blood samples from FcgR transgenic mice were treated with the same proteins and antibodies as in the in vivo study. For human whole blood, isotype controls, soluble CD40L, anti-CD40L mAb including IC in different ratios, soluble CD40, aCD40 mAbs (e.g. CFZ533) including IC in different ratios were used. We observed evidence of thromboembolism (thrombi formation in the lung shown by histopathology) and thrombocytopenia with the soluble CD40L/anti-CD40L mAb IC but not with the soluble proteins or antibodies alone, nor with the soluble CD40/anti-CD40 mAb IC. In vitro platelet aggregation assays performed using blood from FcgR transgenic mice and human healthy donors with recombinant proteins, mAbs and IC from respective species confirmed these findings. These data provide in vivo and in vitro evidence that all anti-CD40 mAbs, either alone or IC with soluble CD40 protein do not induce thromboembolism, indicating that the TE associated with anti-CD40L mAbs are target-related but not co-stimulation pathway specific. Combined with clinical evidence, these data further support the notion of minimal risk for patients developing life-threatening thromboembolic events following administration of a pathway blocking anti-CD40 mAb.